Historical Roots of the Sport of Couples (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article discusses the historical roots of the sport of Kopkari and Kopkari, one of the ancient and traditional sports of the Uzbek people, whose historical roots go back to the culture of the nomadic peoples of Central Asia. This game was mainly closely related to cattle breeding and military training, and tested the courage, agility and team spirit of young men. Kopkari was held in ancient times as part of various ceremonies, weddings and celebrations, in which participants fought for a he-goat (goat or calf) and tried to take it to a designated place. It is argued that this sport has been valued not only as a means of demonstrating physical strength and skill, but also as a means of demonstrating dedication, courage and bravery.